Impact of COVID-19 on Argentina’s Health System: Challenges and Sequelae - Quiroz Mendoza, Flor Consuelo; Guevara Salazar , Kelly Marilyn (SCT Proceedings in Interdisciplinary Insights and Innovations, 2025)
In early 2020, the World Health Organization (WHO) declared Covid-19 an international health emergency, recommending all countries to implement surveillance and control measures. By mid-March, the virus was considered a pandemic. By that time, China was reporting almost all the global cases, with a high number of deaths. The virus arrived in Latin America at the end of February, and soon spread throughout the continent, including Europe and North America. In Peru, Covid-19 appeared in early March, prompting the government to declare a state of emergency and impose social isolation. This highlighted the shortcomings of the Peruvian healthcare system, which was unprepared to deal with the crisis, with a limited number of ICU beds. Covid-19, caused by the SARS-CoV-2 virus, mainly affects the respiratory system. Its transmission occurs mainly by respiratory droplets. The most common symptoms include fever, cough, shortness of breath, and alterations in taste and smell. Although there are no definitive treatments, antivirals, corticosteroids and other drugs are used depending on the patient’s condition. Pneumonia caused by Covid-19 can lead to serious complications, such as multi-organ failure and renal, liver and cardiovascular damage. The nursing care process, based on the NANDA model, is used to guide the care of patients, identifying their needs and establishing intervention plans to improve their health and reintegrate them into the community